Rapid volumetric additive manufacturing in solid state: a demonstration to produce water-content-dependent cooling/heating/water-responsive shape memory hydrogels - Salvekar, Abhijit Vijay (2024)
In this study, we demonstrate the feasibility of rapid volumetric additive manufacturing in the solid state. This additive manufacturing technology is particularly useful in outer space missions (microgravity) and/or for harsh environment (e.g., on ships and vehicles during maneuvering, or on airplanes during flight). A special thermal gel is applied here to demonstrate the concept, that is, ultraviolet crosslinking in the solid state. The produced hydrogels are characterized and the water-content-dependent heating/cooling/water-responsive shape memory effect is revealed. Here, the shape memory feature is required to eliminate the deformation induced in the process of removing the uncrosslinked part from the crosslinked part in the last step of this additive manufacturing process.